Life is an opera made of gestures: a Brechtian reading of Capitu (Urdimento: Revista de Estudos em Artes Cênicas, 2022)
The article relate an analysis of Brechtian gestures like aesthetic value of the Capitu microseries (2008) by Luiz Fernando Carvalho. The aim is to approximate with the appropriate congruences, the gesture dimension of Brecht's epic theater to the audiovisual point of view of adaptation, whose reading path includes the protection of theoretical contributions from Theater Theory, of cinematographic narratology and performance studies, in the analysis of scenes that best align with the critical-interpretative perspective adopted. We begin by broadening the notion of Brechtian gesture, focusing on scenic composition, metafictionality and mise-en-scène. So, gestural aesthetics is read as one of the multiple components of the wide range of expressive signs of the polyvalent language of the microseries, that assimilates different devices and combinations to expand the horizons of meaning.
Keywords: Gestural; Performance; Mise-en-scène; Audiovisual Aesthetics; Capitu